Mass support for conserving 30% of the Earth by 2030: Experimental evidence from five continents - Patrik Michaelsen; Aksel Sundström; Sverker C. Jagers (Proceedings of the National Academy of Sciences, 2025)
Rapid global expansion of protected areas is critical for safeguarding biodiversity but depends on political action for successful implementation. Following widespread ratification of the Kunming-Montreal Global Biodiversity Framework, an unprecedented increase in area-based conservation is required to reach its target of conserving 30% of land, waters, and seas by 2030. These expansions prompt difficult trade-offs between conservation, social, and economic interests. A key factor in securing legitimacy and practical feasibility for expansion regimes is understanding what factors determine public support for them. Using survey and experimental data, we show that in eight countries across five continents, public opinion is 1) strongly in favor of the “30-by-30”-target and 2) highly consistent regarding policy priorities for the design of international- and domestic-level expansion regimes. We find that for international-level policy regimes, support increases with protection responsibilities equally split between countries, rich countries bearing higher costs, more countries actively cooperating, and placement trade not allowed. For domestic-level policy regimes, support generally increases when nature values are prioritized over social or economic values and, in many countries, decreases when costs are borne by a general tax increase, parks are managed by private companies, and when access to parks is restricted. Together, these results demonstrate how protected area expansion policies can be shaped to facilitate reaching 30% protected areas by 2030.